Kadar Hemoglobin (Hb) Antar Trimester pada Ibu Hamil - Bella Andira Safitri (Poltekkes Kemenkes Semarang, 2021)
Hemoglobin functions to transport all oxygen from the lungs to the tissue cells. Hemoglobin contains iron and is still present in red blood cells. In pregnant women hemoglobin levels are often abnormal. According to PMK RI No. 97 of 2014 concerning health services, it stipulates that pregnant women are checked for hemoglobin at least once in the first trimester and once in the third trimester. This is done to determine the condition of pregnant women during pregnancy. Low hemoglobin levels cause anemia. Anemia in pregnant women can affect the process of fetal growth and development in the womb. The purpose of this study was to determine the hemoglobin level between trimesters in pregnant women at the Jatilawang Health Center, Banyumas Regency in 2020. The research criteria was a descriptive study using a retrospective time series design using secondary data. The results of inter-trimester hemoglobin levels in pregnant women at the Jatilawang Health Center, Banyumas Regency in 2020 are in the first trimester 40% normal hemoglobin levels and 60% abnormal hemoglobin levels, in the second trimester hemoglobin levels are 72% normal and 28% hemoglobin levels are not normal, in the second trimester the hemoglobin levels are normal and 28% are abnormal. III 96% normal hemoglobin level and 4% abnormal hemoglobin level. Inter-trimester hemoglobin levels in pregnant women at the Jatilawang Health Center, Banyumas Regency in 2020 tend to be higher based on trimesters I, II and III.